1997
DOI: 10.1080/135468097396342
|View full text |Cite
|
Sign up to set email alerts
|

Phonological Short-term Memory and its Relationship to Language in Williams Syndrome

Abstract: Williams syndrome (WS), a rare neurodevelopmental disorder of genetic origin, is characterised by a relative advantage of language over more serious deficits in other cognitive domains. In this study the relationship of phonological short-term memory to WS language, in particular vocabulary, was explored. Using Gathercole and Baddeley's Children's Test of Nonword Repetition (CNRep) (Gathercole & Baddeley, 1996), we examined the pattern of performance by WS participants on that task and compared it to performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 111 publications
(84 citation statements)
references
References 28 publications
2
82
0
Order By: Relevance
“…One possibility, considered earlier, is that language differences in recall reflect the use of long-term knowledge to support recall performance. Within a particular language it is consistently found that familiar words are recalled better than are unfamiliar nonwords (Hulme et al, 1991) and that highly wordlike nonwords are more accurately recalled than non-wordlike nonwords (Gathercole, 1995;Gathercole et al, 1999;Gathercole et al, 1991;Grant et al, 1997;van Bon & van der Pijl, 1997). It has been suggested that these phenomena arise from the use of long-term representations of phonological information, both of the phonological structure of specific lexical items and of the phonotactic properties of a language , to support the recall of degraded memory traces held in the phonologicalstore.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…One possibility, considered earlier, is that language differences in recall reflect the use of long-term knowledge to support recall performance. Within a particular language it is consistently found that familiar words are recalled better than are unfamiliar nonwords (Hulme et al, 1991) and that highly wordlike nonwords are more accurately recalled than non-wordlike nonwords (Gathercole, 1995;Gathercole et al, 1999;Gathercole et al, 1991;Grant et al, 1997;van Bon & van der Pijl, 1997). It has been suggested that these phenomena arise from the use of long-term representations of phonological information, both of the phonological structure of specific lexical items and of the phonotactic properties of a language , to support the recall of degraded memory traces held in the phonologicalstore.…”
Section: Discussionmentioning
confidence: 98%
“…The superior recall of words over nonwords has led to the suggestion that immediate memory performance is in some way enhanced by prior phonologically based lexical knowledge; nonwords are unable to benefit from such support because no long-term representation exists for unfamiliar word forms (Hulme et al, 1991). A second type of long-term knowledge support relates to knowledge concerning the phonotactic properties of a language; for unfamiliar words (or nonwords whose phonological structure conforms to the phonotactics of the language), those items that contain high-probability phoneme combinations are better recalled than those containing low-probability phoneme combinations (Gathercole, Frankish, Pickering, & Peaker, 1999; see also Gathercole, 1995;Gathercole, Willis, Emslie, & Baddeley, 1991;Grant et al, 1997;van Bon & van der Pijl, 1997).…”
mentioning
confidence: 99%
“…Phillips, Jarrold, Baddeley, Grant, & Karmiloff-Smith, 2004), comparisons of the verbal and performance IQ scores of individuals with WS have generally shown a verbal superiority (e.g. Grant et al, 1997;Levy & Bechar, 2003). Individuals with DS usually display "flatter" profiles (Jarrold, Baddeley, & Phillips, 2007), but have often exhibited expressive language difficulties (e.g.…”
Section: Aetiological and Cognitive Characteristics Of Williams And Dmentioning
confidence: 99%
“…NWR tasks have been used with many clinical populations (Gathercole, 2006;Bishop et al, 2006;Conti-Ramsden et al, 2001;Grant et al, 1997;Laws & Gunn, 2004;Graf-Estes et al, 2007) and across languages (Sahlen et al, 1999;reviewed in Coady & Evans, 2008). However, there is no current consensus about which underlying skills, including sensorimotor skills, contribute to NWR performance, and in what proportion (Coady & Evans, 2008;Snowling et al, 1981Snowling et al, , 1986.…”
Section: Articulating Novel Words: Children's Oromotor Skills Predictmentioning
confidence: 99%